Price Competition in Five-Star Hotel Industry - Eko Atmadji; Indra Putra Nugraha (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2022)
Purpose – To analyze the characteristics of price competition in five-star hotel industry in DIY. Method – Descriptive qualitative method in order to know the detail about price competition. In-depth interviews with market players as well as government and other stakeholders are conducted. To get the full picture, this study also interviewed to PHRI (Indonesian Hotel Union). The SCP theory (structure-conduct-performance) becomes the guidance of interview and analysis. Findings – The results of this study indicate that the hotel market is loose oligopoly or close to the monopolistic nature, competition is quite strict considering frequent over supply within one year, and pricing strategy becomes more important. Every hotel often changes their price strategy to follow certain conditions in the market. In differentiating its products, each hotel implements different themes to attract the attention of the guests. In five-star hotels at DIY, price strategy has low impact to the customers’ satisfaction except for Eastparc Hotel. Implication – This study implicates that the behavior of five-star hotels in DIY will make the competition become soft and create tacit collusion. This is not good news for below three-star rank hotels. Originality – This study contributes to the price competition study especially in five-star hotel market. Abstrak Tujuan – Menganalisis karakteristik persaingan harga pada industri hotel bintang lima di DIY. Metode – Metode kualitatif deskriptif untuk mengetahui secara detail tentang persaingan harga. Wawancara mendalam dengan pelaku pasar serta pemerintah dan pemangku kepentingan lainnya dilakukan. Untuk mendapatkan gambaran yang utuh, penelitian ini juga mewawancarai PHRI (Persatuan Hotel Indonesia). Teori SCP (struktur-perilaku-kinerja) menjadi pedoman wawancara dan analisis. Temuan – Hasil penelitian ini menunjukkan bahwa pasar perhotelan bersifat oligopoli longgar atau mendekati sifat monopolistik, persaingan cukup ketat mengingat sering terjadi over supply dalam satu tahun, dan strategi penetapan harga menjadi lebih penting. Setiap hotel sering mengubah strategi harga mereka untuk mengikuti kondisi tertentu di pasar. Dalam membedakan produknya, setiap hotel menerapkan tema yang berbeda untuk menarik perhatian para tamu. Di hotel bintang lima di DIY, strategi harga berdampak rendah terhadap kepuasan pelanggan kecuali Hotel Eastparc. Implikasi – Studi ini berimplikasi bahwa perilaku hotel bintang lima di DIY akan membuat kompetisi menjadi lunak dan menciptakan tacit collusion. Ini bukan kabar baik untuk hotel peringkat bintang tiga atau lebih rendah. Orisinalitas – Studi ini berkontribusi pada studi persaingan harga terutama di pasar hotel bintang lima.